Determinants of entrepreneurial intention: The case of UUM's business undergraduates - Wan Zhalkiatul Aida, lshak (2015)
Due to the inclination numbers of Malaysia‟s entrepreneurs nowadays, the youth have shown a great involvement in entrepreneurship and have been one of the biggest contributors to the country‟s economic growth. As this emergence took place, it is crucial for the related stakeholders such as government, educational agencies and policy makers to keep on encouraging the youth in Malaysia to participate in any entrepreneurship activities. Thus, it is important to understand the factors that will influence the intention to start up the business among the youth especially among university students. The main objective of this study is to analyze the relationship between risk taking propensity, family support, self-efficacy and entrepreneurship education with the entrepreneurial intention among the undergraduates under the School of Business Management, Universiti Utara Malaysia. Data was collected by using the questionnaire that has been distributed to 260 respondents; however, only 200 questionnaires have been successfully collected for the data analysis. Findings of the research revealed that only two (2) out of four variables having significant relationship with the entrepreneurial intention, which are self-efficacy and entrepreneurship education. The recommendation for the related stakeholders and future research were also discussed